Advanced light microscopy core facilities: Balancing service, science and career. Issue 6 (4th April 2016) - Ferrando‐May, Elisa; Hartmann, Hella; Reymann, Jürgen; Ansari, Nariman; Utz, Nadine; Fried, Hans‐Ulrich; Kukat, Christian; Peychl, Jan; Liebig, Christian; Terjung, Stefan; Laketa, Vibor; Sporbert, Anje; et al.
ABSTRACT: Core Facilities (CF) for advanced light microscopy (ALM) have become indispensable support units for research in the life sciences. Their organizational structure and technical characteristics are quite diverse, although the tasks they pursue and the services they offer are similar. Therefore, throughout Europe, scientists from ALM‐CFs are forming networks to promote interactions and discuss best practice models. Here, we present recommendations for ALM‐CF operations elaborated by the workgroups of the German network of ALM‐CFs, German Bio‐Imaging (GerBI). We address technical aspects of CF planning and instrument maintainance, give advice on the organization and management of an ALM‐CF, propose a scheme for the training of CF users, and provide an overview of current resources for image processing and analysis. Further, we elaborate on the new challenges and opportunities for professional development and careers created by CFs. While some information specifically refers to the German academic system, most of the content of this article is of general interest for CFs in the life sciences. Microsc. Res. Tech. 79:463–479, 2016 . © 2016 THE AUTHORS MICROSCOPY RESEARCH AND TECHNIQUE PUBLISHED BY WILEY PERIODICALS, INC.